Magnetohydrodynamiczne łożysko ślizgowe w stycznym polu magnetycznym - AGRAWAL, V.K. (Engineering Transactions, 1970)
Magnetohydrodynamic slider bearing with tangential magnetic fieldThe load capacity of slider bearing with tangential magnetic field is investigated. The optimum profile is found to be step form with the riser location and step height ratio depending on the applied magnetic field.Further it is seen that the load capacity is increased' by the application of magnetic field.